Solidarity as a Public Virtue?: Law and Public Policies in the European Union - Lahusen, Christian; Federico, Veronica (Transnational Perspectives on Transformations, 2018)
This volume is dedicated to the principle of solidarity. It examines the role of solidarity as a legal principle and as a component of public policies in eight European countries Denmark, France, Germany, Greece, Italy, Poland, Switzerland and the UK and at the level of the European Union. It particularly focuses on developments in three areas: unemployment, immigration and asylum, and disability.